Ubiquitous information technologies and applications CUTE 2012 / Youn-Hee Han [and others], editors. - Han, Youn-Hee (Lecture notes in electrical engineering, 2013)
This book is for The 7th International Conference on Ubiquitous Information Technologies and Applications (CUTE 2012). Ubiquitous computing will require a new approach to fitting technology to our lives. The advent of new computing devices, and the seamless connectivity between these devices, thanks to diverse wired and wireless networks, are enabling new opportunities for a user to perform his/her operation all the time and everywhere. These seamlessly connected devices are ranging from mobile handset to wearable computers. Also, it is expected that these devices will become so pervasive that they will be embedded in the surrounding physical environment, and transparent and invisible to a user. Such devices, whether carried on by people or embedded into other systems, will constitute a global internetworking infrastructure and likely to provide a new level of openness and dynamics. Ubiquitous computing has as its goal the enhancing computer use by pushing computational services out of conventional desktop interfaces into physical environments, but effectively making them transparent forms and calm mode of interactivity. Recent advances in electronic and computer technologies have paved the way for the proliferation of ubiquitous computing and innovative applications that incorporate these technologies. This book covers the following topics: Ubiquitous Communication and Networks Ubiquitous System and Application Security on Ubiquitous Computing Systems Smart Devices and Applications Cloud and Grid Systems Service-oriented and Web Service Computing Embedded Hardware Image Processing and Multimedia Ubiquitous Software Technology.